Activation of hip and knee muscles during two landing tasks performed by male volleyball athletes - Leporace, Gustavo; Praxedes, Jomilto [UNESP]; Pereira, Glauber Ribeiro; Chagas, Daniel; Pinto, Sérgio; Batista, Luiz Alberto (FapUNIFESP (SciELO), 2011)
Objective: To compare the myoelectric activity before and after ground contact between single-leg (SL) and double-leg (DL) landings in male athletes. Participants: Fifteen male volleyball athletes without signs and symptoms of lesions in the lower extremities, with a minimum of three years experience in the sport (13 ± 1 years, 1.70 ± 0.12 m, 60 ± 12 kg). Measurements: Participants performed two vertical jumps, landing unilaterally and bilaterally. The myoelectric activity of the rectus femoris (RF), biceps femoris (BF), hip adductors (HA) and the BF/RF ratio were compared between the two landings and between the phases characterized by 100ms before (PRE) and after 100 ms (POST) ground contactusing ANOVA two-way test with post hoc test of Bonferroni (α = 5%). Results: In both landings activation of RF was higher in the POST in relation to the PRE (p <0.0001). Comparing the landings in the same phase statistical differences (p = 0.2212) were not found. Although the BF did not present significant differences between the PRE and POST in each landing (p = 0.2321), its activation was higher in SL (p = 0.0051). The HA showed greater activation in the POST during the SL (p = 0.0013), however there were no differences when comparing the two landings (p = 0.9233). The BF/RF ratio was higher in both landings during PRE (p = 0.0012). Nevertheless, no differences between the landings (p = 0.7037) were found. Conclusion: The results suggest that each muscle has a different role during landing tasks in men. While RF has the main function to decelerate the knee and the downward movement, characterized by increased activation in the POST, BF seems to attenuate the loads on the knee in activities of higher impact, staying more active throughout the cycle in the SL. The increased activation of HA after ground contact in the SL highlights the importance of core region in stabilizing the pelvis in situations of great instability. Further studies are needed to determine the effects of muscle activation at the imposition of mechanical load on the knee that are potentially harmful to male athletes.
Keywords: Anterior cruciate ligament; Biomechanics; EMG; Males; Risk factor